Magnetic proximity-enhanced Curie temperature of Cr-doped Bi₂Se₃ thin films - Baker, AA; Figuorea, AI; Kummer, K; Collins-McIntyre, LJ; Hesjedal, T; van der Laan, G (American Physical Society, 2015)
We report a study on the transition temperature, T_C, of a Cr-doped Bi2Se3 topological insulator thin film, where an increase in the ferromagnetic onset can provide a pathway towards low-power spintronics applications. Arrott plots, obtained by Cr L_2,3 x-ray magnetic circular dichroism as a function of field at various low temperatures, give a T_C ~7 K. This is similar to the bulk value of the sample, which means that there is no indication the spontaneous magnetization is different near the surface. Evaporation of a thin layer of Co onto the pristine surface of the in-situ cleaved sample increases the ordering temperature to ~19 K. X-ray absorption spectroscopy shows that Cr enters the Bi2Se3 host matrix in a divalent state, and is unchanged by the Co deposition.